The Impact of the home country on internationalization - Cuervo-Cazurra, A.; Luo, Yadong; Ramamurti, R.; Ang, S. (Pergamon, 2018)
© 2018 Elsevier Inc. We analyze how a firm's home country influences its internationalization. We propose two complementary types of influence. First, we conceptualize a firm's international trade as shaped by four drivers: comparative advantage, comparative disadvantage, country-of-origin advantage, and country-of-origin liability. Second, we conceptualize the firm's foreign direct investment as shaped by four other drivers: institutional learning, competitive learning, institutional escape, and competitive escape. Taken together, these eight drivers help pull together recent theoretical advances on topics such as emerging-market multinationals, investment in tax havens, and cross-border acquisitions of firms in advanced countries. We also highlight other home-country related issues, such as strategic responses and home-host country links, in the spirit of fostering future research on home-country effects that warrant a more nuanced understanding.